Nature of Science Lessons, Argumentation and Scientific Discussions among Students in Science Class: A Case Study in a Successful School - Elif Ozturk; Sukran Ucus (Journal of Education in Science, Environment and Health)
Argumentation is highlighted as one of the most important activities of science education by many researchers. The main aim of this research is to examine primary school students’ nature of science classes and argumentation skills in terms of their academic success in primary science classes. Thus, the specific interest of the study is centered on the nature of science lessons, the structure of the argument and an effort to scaffold students’ understanding concerning the argument’s structure. As this was considered the initial, but students have to acquire fundamental skills before dealing with the inner validity of an argument. Moreover, successful and labeled students for this study were put under the microscope curiously by the researchers. Within the scope of this purpose, the study was designed on qualitative research techniques which are detailed as explorative and fundamentally interpretation for the related issue. Since a particular school’s successful students are considered in the research, it could be viewed and designed as a case study. The study is conducted with 8th graders with the age of 12-13 in a private elementary school. Focus group interviews and classroom observations during science lessons were the basic tools to obtain data. The results were grouped under the following aspects: objectives of science education, science teaching methods of teachers in their science class, materials used while teaching and teachers’ approaches for being successful in science. Science teachers in this school are both give importance in order to inquiry for teaching science. This research has demonstrated that even the most successful 8th graders in science classes do not necessarily apprehend fundamental concepts about nature and science. The science teachers in this research also mentioned that the interactive nature of information technologies can support students in carrying out inquiry-based activities, using topics, questions, and even theories that they themselves define and develop argumentation.